Getting to the (square) root of the problem - Haefele, Alexandre (2012)
We present experimental data illustrating that photochemical upconversion based on sensitized triplet–triplet annihilation can exhibit anti-Stokes emissions whose intensities with respect to the excitation power can vary between quadratic and linear using a noncoherent polychromatic light source. The benchmark upconverting composition consisting of Pd(II) octaethylporphyrin (PdOEP) sensitizers and 9,10-diphenylanthracene (DPA) acceptors/annihilators in toluene was selected to generate quadratic, intermediate, and linear behavior under both coherent and noncoherent excitation conditions. Each of these power laws was traversed in a single sample in one contiguous experiment through selective pumping of the sensitizer using an Ar+ laser. Wavelength-dependent responses ranging from quadratic to pseudolinear were also recorded from the identical sample composition when excited by Xe lamp/monochromator output in a conventional fluorimeter, where the optical density at λex dictates the observed incident power dependence. Finally, pure linear behavior was derived from noncoherent excitation for the first time at higher sensitizer concentrations.